Involvement of Cathepsins in Innate and Adaptive Immune Responses in Periodontitis. (31st March 2020) - Yan, Xu; Wu, Zhou; Wang, Biyao; Yu, Tianhao; Hu, Yue; Wang, Sijian; Deng, Chunfu; Zhao, Baohong; Nakanishi, Hiroshi; Zhang, Xinwen
Abstract : Periodontitis is an infectious disease whereby the chronic inflammatory process of the periodontium stimulated by bacterial products induces specific host cell responses. The activation of the host cell immune system upregulates the production of inflammatory mediators, comprising cytokines and proteolytic enzymes, which contribute to inflammation and bone destruction. It has been well known that periodontitis is related to systemic inflammation which links to numerous systemic diseases, including diabetes and arteriosclerosis. Furthermore, periodontitis has been reported in association with neurodegenerative diseases such as Alzheimer's disease (AD) in the brain. Regarding immune responses and inflammation, cathepsin B (CatB) plays pivotal role for the induction of IL-1 β, cathepsin K- (CatK-) dependent active toll-like receptor 9 (TLR9) signaling, and cathepsin S (CatS) which involves in regulating both TLR signaling and maturation of the MHC class II complex. Notably, both the production and proteolytic activities of cathepsins are upregulated in chronic inflammatory diseases, including periodontitis. In the present review, we focus on the roles of cathepsins in the innate and adaptive immune responses within periodontitis. We believe that understanding the roles of cathepsins in the immune responses in periodontitis would help to elucidate the therapeutic strategies of periodontitis, thus benefit for reduction of systemic diseases as well as neurodegenerative diseases in the global aging society.